‘The Jew of Venice’ (1701): il primo Shylock dopo Shakespeare - Maria Chiara Barbieri (Drammaturgia, 2022)
The scenic fortune of The Merchant of Venice marks a turning point in 1741 thanks to the interpretation of the character of Shylock by the actor Charles Macklin, consecrated by Alexander as ‘the Jew that Shakespeare drew’. A recognition of the actor’s value, but also a sign of distance from The Jew of Venice, the adaptation by George Granville with which in 1701 the comedy that had been missing from the stage for almost a century was revived, albeit in a modified form. The essay analyses the genesis and compositional structure of the adaptation in which Granville seeks a mediation between the aim for ‘regularization’ in the classicist sense of the Shakespearean text and the desire to preserve its essence, ‘the silver at the bottom of the melting pot’. Consistent with these purposes is the assignment of the part of Shylock to the comic actor Thomas Doggett, whose artistic and character profile is outlined through many testimonies of long-time companions. On the other hand, the iconographic testimonies are few, though for the first time they are examined together with an engraving contained in the first modern edition of Shakespearean Works published in 1709. The comparison leads to hypothesize that the first existing image of the character of Shylock is also the first to portray an actor, Thomas Doggett.